Double-passivator perovskite solar cell and preparation method thereof

By using passivating agents such as PEACl, PEAI and BAI in perovskite solar cells to collaborate in passivating the perovskite absorbing layer, the problem that a single passivating agent cannot effectively passivate various defects is solved, and perovskite is improved The output power and life of solar cells achieve high efficiency perovskite solar cell preparation.

CN119300616APending Publication Date: 2025-01-10HUANENG QINGHAI POWER GENERATION CO LTD +1

Patent Information

Application Number
CN202411417804.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing perovskite solar cells cannot effectively passivate various defects due to the inability of a single passivator to passivate various defects, resulting in low battery efficiency and short life.

Method used

Use one or more passivating agents mixed with m-F-PEAI, including PEAC1, PEAI and BAI as the passivation layer to passivate the perovskite absorbing layer, and passivate more types of them through different ions or related groups. Defects, improve material stability and charge transfer efficiency.

Benefits of technology

It improves the output power and service life of perovskite solar cells, simplifies the preparation process, reduces the equipment conditions requirements, and realizes the preparation of high-efficiency perovskite solar cells, with a battery efficiency of up to 23.66%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119300616A_ABST
    Figure CN119300616A_ABST
Patent Text Reader

Abstract

The invention relates to the field of perovskite solar cell preparation, in particular to a double-passivator perovskite solar cell and a preparation method thereof, and the solar cell adopts a mixture of one or more of phenethyl amine chloride phenethylamine iodine and n-butylammonium iodide and m-fluorophenethylamine iodine as a passivator to passivate a perovskite light absorption layer. According to the invention, through the synergistic passivation of the double passivators of the perovskite light absorption layer, more types of defects can be passivated by using different ions or related groups, so that effective passivation is realized, and the output power of the solar cell is improved. Wherein m-F-PEAI not only can assist other passivators in passivating defects on the surface of the perovskite material, reduce non-radiative recombination and improve the stability of the perovskite material, but also can improve interface contact between the perovskite absorption layer and other functional layers, reduce interface recombination and improve charge transfer efficiency. The problems that an existing single passivator is single in passivation defect type, various defects cannot be effectively passivated, the passivation efficiency is poor, and the battery efficiency is low are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of perovskite solar cell preparation, in particular to a double-passivator perovskite solar cell and a preparation method thereof. Background Art

[0002] Perovskite is the name of a mineral. It was first discovered by Rose in 1839 in Russian ores and named after the Russian geologist Lev Perovski. Its chemical composition is CaTiO3, hence the name perovskite. Perovskite in a narrow sense refers to the calcium titanate mineral itself, while perovskite in a broad sense refers to ABX3-type compounds with a perovskite structure. Now perovskite usually refers to compounds with a perovskite structure.

[0003] Perovskite has gradually become one of the research focuses of multiple disciplines such as physics, chemistry and materials. In 2009, scientists first used perovskite materials CH3NH3PbI3 and CH3NH3PbBr3 as sensitizers in dye-sensitized solar cells and achieved a photoelectric conversion efficiency of about 4%. This exciting result paved the way for the development of a new topic at the forefront of current research - high-efficiency perovskite photovoltaic technology. In the past decade, its photoelectric conversion efficiency has increased from the initially reported 4% to more than 20% today, catching up with the efficiency of polycrystalline silicon solar cells that have been developed for 65 years, thus becoming the new generation of solar cell technology with the most promising commercial application prospects.

[0004] Existing perovskite cells generally have five layers from the top transparent electrode (indium tin oxide ITO, fluorine-doped tin oxide FTO) where light is incident to the bottom electrode, which are transparent conductive metal oxide glass electrode layer, carrier electron or hole transport layer, perovskite material layer, carrier hole or electron transport layer and metal electrode layer. The traditional five-layer structure of perovskite cells has the characteristics of simple manufacturing process and simple operation steps, but because there are often a large number of defects on the surface and grain boundaries of perovskite films, these defects will become non-radiative recombination centers. The perovskite material layer is in direct contact with the carrier transport layer. When under light conditions, the I in the perovskite material - , Pb 2+ Ion migration will occur, moving to the hole transport layer and the electron transport layer respectively, reacting to become a single substance, causing the degradation of the perovskite material; at the same time, the metal atoms at the electrode will diffuse into the perovskite material layer, causing the electrode thickness to become thinner, the series resistance to increase, resulting in energy loss, reduced output power, and shortened life.

[0005] The invention with publication number CN116685158A discloses a perovskite cell and preparation method using 12-HSA passivation perovskite layer, wherein a 12-HSA solution mixed with 12-hydroxystearic acid and isopropyl alcohol is applied on the perovskite layer to form a passivation layer, a physical protective layer is formed on the perovskite layer, the defect state density of the perovskite transport layer is reduced, and the long-term stability and moisture resistance of the perovskite cell device are improved. That is, a single bulk passivator is used to passivate the surface of the perovskite layer to reduce defects, thereby reducing the non-radiative recombination rate and improving the photoelectric conversion efficiency. Although the efficiency of perovskite solar cells using a single bulk passivator has been significantly improved compared to those without a bulk passivator, the single passivator has a single passivation defect type, and various defects cannot be effectively passivated, the passivation efficiency is poor, and the battery efficiency is low. Summary of the invention

[0006] In view of the problems in the prior art that a single passivator has a single passivation defect type, cannot effectively passivate various defects, has poor passivation efficiency, and has low battery efficiency, the present invention provides a double passivator perovskite solar cell and a preparation method thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The invention provides a double-passivator perovskite solar cell, which adopts a passivator including one or more of PEACl, PEAI and BAI mixed with mF-PEAI as a passivation layer to passivate the perovskite light-absorbing layer.

[0008] Furthermore, it also includes a substrate and a hole transport layer, a self-assembled monolayer, a perovskite light absorption layer, an electron transport layer and a top electrode arranged in sequence on the substrate; the passivation layer is arranged between the perovskite light absorption layer and the electron transport layer.

[0009] Furthermore, the substrate is a transparent conductive glass substrate.

[0010] Furthermore, the hole transport layer is NiO x , CuSCN or CuI, where the value of x is 1 to 1.5.

[0011] Furthermore, the self-assembled monolayer is one or more of MeO-2PACz, 2PACz, Me-4PACz and 4PACz.

[0012] Furthermore, the perovskite light absorbing layer is (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3.

[0013] Furthermore, the electron transport layer is one of TiO2, SnO2, fullerene and fullerene derivatives.

[0014] Furthermore, the top electrode is gold, silver, copper, graphite or amorphous carbon.

[0015] Furthermore, the thickness of the passivation layer is 1-5 nm.

[0016] The present invention also provides a method for preparing a double-passivator perovskite solar cell, comprising: preparing a hole transport layer on a substrate; preparing a self-assembled monolayer on the hole transport layer; Preparation of perovskite light absorbing layer on self-assembled monolayer; On the perovskite light absorbing layer, a passivation layer is prepared using a passivation agent including one or more of PEACl, PEAI and BAI mixed with mF-PEAI; preparing an electron transport layer on the passivation layer; A top electrode is prepared on the electron transport layer to obtain a double-passivator perovskite solar cell.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a double passivator perovskite solar cell, wherein the solar cell adopts a passivator including one or more of phenethylammonium chloride, phenethylamine iodide and n-butylammonium iodide mixed with m-fluorophenethylamine iodine as a passivation layer to passivate the perovskite light-absorbing layer. By adopting one or more of PEACl, PEAI and BAI in coordination with mF-PEAI to passivate the perovskite light-absorbing layer, different ions or related groups can be used to passivate more types of defects, thereby achieving better passivation, and further improving the output power of the solar cell. Among them, mF-PEAI can not only assist other passivators in passivating the defects on the surface of perovskite materials, reduce non-radiative recombination, improve the stability of perovskite materials, and extend the service life of solar cells, but also improve the interface contact between the perovskite absorption layer and other functional layers, reduce interface recombination, and improve charge transfer efficiency. In some cases, mF-PEAI may induce structural changes in perovskite materials, such as the formation of a two-dimensional perovskite phase, which helps to optimize the photoelectric properties and stability of perovskite materials, and can simplify the preparation process of perovskite cells, reduce the conditions required for equipment, and help achieve large-scale production of perovskite solar cells.

[0018] The present invention also provides a method for preparing a double-passivator perovskite solar cell, which comprises the following steps: sequentially preparing a hole transport layer, a self-assembled monolayer, and a perovskite light-absorbing layer on a substrate; then preparing a passivation layer using a passivator mixed with one or more of PEACl, PEAI, and BAI and mF-PEAI; and finally sequentially preparing an electron transport layer and a top electrode on the passivation layer, thereby achieving successful preparation of a double-passivator perovskite solar cell. The preparation method is simple and has relatively low condition requirements. The efficiency of the prepared perovskite solar cell can reach 23.66%, further providing a good premise for the application of perovskite cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic structural diagram of a double passivator perovskite solar cell of the present invention.

[0020] Figure 2 The present invention is a flow chart of a method for preparing a double-passivator perovskite solar cell.

[0021] Among them, 1-substrate, 2-hole transport layer, 3-self-assembled monolayer, 4-perovskite light absorption layer, 5-passivation layer, 6-electron transport layer, 7-top electrode. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0023] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0024] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible sub-ranges and individual values ​​within the ranges.

[0025] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0026] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0027] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0028] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0029] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0030] Example 1 The invention discloses a double-passivator perovskite solar cell, which adopts a passivator including one or more of PEACl, PEAI and BAI mixed with mF-PEAI as a passivation layer 5 to passivate a perovskite light-absorbing layer 4.

[0031] By depassivating the perovskite light absorbing layer 4 with a passivating agent mixed with one or more of PEACl, PEAI and BAI and mF-PEAI, the surface defect types of the perovskite light absorbing layer 4 can be enriched, and while achieving effective passivation, the interface contact between the perovskite light absorbing layer 4 and other functional layers can be improved, the interface recombination can be reduced, the charge transfer efficiency can be improved, the photoelectric performance and stability of the perovskite material can be optimized, and the output power and service life of the battery can be further improved.

[0032] Example 2 See also Figure 1 The present invention discloses a double passivator perovskite solar cell, comprising a substrate 1 and a hole transport layer 2, a self-assembled monolayer 3, a perovskite light absorption layer 4, a passivation layer 5, an electron transport layer 6 and a top electrode 7 sequentially arranged on the substrate 1; Wherein, the substrate 1 is a transparent conductive glass substrate; The hole transport layer 2 is NiO x , CuSCN or CuI, wherein the value of x is 1 to 1.5; The self-assembled monolayer 3 is one or more of MeO-2PACz, 2PACz, Me-4PACz and 4PACz; The perovskite light absorbing layer 4 is (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3; The passivation layer 5 is prepared by using a passivation agent including one or more of PEACl, PEAI and BAI mixed with mF-PEAI; The electron transport layer 6 is one of TiO2, SnO2, fullerene and fullerene derivatives; The top electrode 7 is made of gold, silver, copper, graphite or amorphous carbon.

[0033] The transparent conductive glass substrate is indium tin oxide, the thickness of the substrate 1 is 200-400nm; the thickness of the hole transport layer 2 is 20-40nm; the thickness of the self-assembled monolayer 3 is 1-5nm; the thickness of the perovskite light absorption layer 4 is 300-700nm; the thickness of the passivation layer 5 is 1-5nm; the thickness of the electron transport layer 6 is 10-100nm; the thickness of the top electrode 7 is 50-500nm.

[0034] Example 3 See also Figure 2 The present invention provides a method for preparing a double-passivator perovskite solar cell, which comprises: S1: preparing a hole transport layer 2 on a substrate 1; the substrate 1 is a transparent conductive glass substrate, the transparent conductive glass substrate is indium tin oxide, and the thickness of the substrate 1 is 200-400 nm; the hole transport layer 2 is NiO x , CuSCN or CuI, wherein the value of x is 1 to 1.5, the thickness is 20 to 40 nm, and the specific method is: NiO was prepared on substrate 1 by magnetron sputtering. x , CuSCN or CuI layer, and annealing at 300°C to 350°C for 25 to 35 minutes to form a hole transport layer 2.

[0035] S2: preparing a self-assembled monolayer 3 on the hole transport layer 2; the self-assembled monolayer 3 is one or more of MeO-2PACz, 2PACz, Me-4PACz and 4PACz, with a thickness of 1 to 5 nm, and the specific method is: One or more of MeO-2PACz, 2PACz, Me-4PACz and 4PACz are used in isopropanol as solvent to prepare a self-assembled monolayer spin-coating liquid with a concentration of 0.25-0.35 g / mL, and the self-assembled monolayer spin-coating liquid is spin-coated on the hole transport layer 2 at a rotation speed of 2500-3500 rpm, and annealed at 95°C-120°C for 8-15 minutes to form a self-assembled monolayer 3.

[0036] S3: preparing a perovskite light absorbing layer 4 on the self-assembled monolayer 3; the perovskite light absorbing layer 4 is (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3, the thickness is 300~700nm, the specific method is: A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 perovskite precursor solution, at 2000 ~ 5000rpm conditions (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is spin-coated on the self-assembled monolayer 3. Before the spin coating is completed, chlorobenzene is added as an anti-solvent. Annealing is performed at 95°C to 120°C for 25 to 35 minutes to form a perovskite light-absorbing layer 4.

[0037] S4: On the perovskite light-absorbing layer 4, a passivation layer 5 is prepared using a passivator including one or more of PEACl, PEAI and BAI mixed with mF-PEAI; using isopropyl alcohol as a solvent, one or more solutions of PEACl, PEAI and BAI and an mF-PEAI solution with a concentration of 0.5 mg / mL are prepared respectively, and the two are mixed in a volume ratio of 1:1 to form a passivation agent; the passivation agent is spin-coated on the perovskite light-absorbing layer 4 at a rotation speed of 2500-3500 rpm, and annealed at 95°C-120°C for 8-15 min to form a passivation layer 5.

[0038] S5: preparing an electron transport layer 6 on the passivation layer 5; the electron transport layer 6 is one of TiO2, SnO2, fullerene and fullerene derivatives, with a thickness of 10 to 100 nm, and the specific method is as follows: The electron transport layer 6 is prepared on the passivation layer 5 by vacuum evaporation.

[0039] S6: preparing a top electrode 7 on the electron transport layer 6 to obtain a double passivator perovskite solar cell; the top electrode 7 is gold, silver, copper, graphite or amorphous carbon, and has a thickness of 50 to 500 nm. The specific method is: A top electrode 7 is prepared on the electron transport layer 6 by vacuum plating to obtain a double passivator perovskite solar cell.

[0040] Example 4 On a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 300 nm, NiO is sputtered by magnetron sputtering. x , the value of x is 1 to 1.5, and annealing is performed at 300° C. for 30 min to prepare a hole transport layer 2 with a thickness of 30 nm.

[0041] Using isopropanol as solvent, MeO-2PACz was prepared into a self-assembled monolayer spin coating liquid with a concentration of 0.3 g / mL, and the self-assembled monolayer spin coating liquid was spin coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 min to form a self-assembled monolayer 3 with a thickness of 2 nm.

[0042] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, take 100 μL (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm for 40 seconds. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 400 nm.

[0043] Using isopropanol as solvent, prepare PEACl solution and mF-PEAI solution with a concentration of 0.5 mg / mL respectively, and mix the two in a volume ratio of 4:1 to form a passivator; spin-coat the passivator on the perovskite light-absorbing layer 4 at a rotation speed of 3000 rpm, and anneal for 10 minutes at 100° C. to form a passivation layer 5 with a thickness of 2 nm.

[0044] A C layer with a thickness of 40 nm was prepared on the passivation layer 5 by vacuum evaporation. 60 , as the electron transport layer 6.

[0045] Gold with a thickness of 100 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0046] Example 5 CuSCN was sputtered on a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 290 nm by magnetron sputtering, and annealed at 350° C. for 25 min to prepare a hole transport layer 2 with a thickness of 26 nm.

[0047] Using isopropanol as solvent, Me-4PACz was prepared into a self-assembled monolayer spin coating liquid with a concentration of 0.31 g / mL, and the self-assembled monolayer spin coating liquid was spin coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 min to form a self-assembled monolayer 3 with a thickness of 1 nm.

[0048] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, take (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 500 nm.

[0049] Using isopropanol as solvent, prepare PEACl solution and mF-PEAI solution with a concentration of 0.5 mg / mL respectively, and mix the two in a volume ratio of 3:1 to form a passivator; spin-coat the passivator on the perovskite light-absorbing layer 4 at a rotation speed of 3000 rpm, and anneal for 10 minutes at 100° C. to form a passivation layer 5 with a thickness of 1 nm.

[0050] A C layer with a thickness of 50 nm was prepared on the passivation layer 5 by vacuum evaporation. 60 , as the electron transport layer 6.

[0051] Gold with a thickness of 200 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0052] Example 6 CuI was sputtered on a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 320 nm by magnetron sputtering, and annealed at 250° C. for 35 min to prepare a hole transport layer 2 with a thickness of 35 nm.

[0053] Using isopropanol as solvent, Me-4PACz was prepared into a self-assembled monolayer spin coating liquid with a concentration of 0.32 g / mL, and the self-assembled monolayer spin coating liquid was spin coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 min to form a self-assembled monolayer 3 with a thickness of 3 nm.

[0054] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 perovskite precursor solution, take (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 350 nm.

[0055] Using isopropanol as solvent, prepare PEACl solution and mF-PEAI solution with a concentration of 0.5 mg / mL respectively, and mix the two in a volume ratio of 2:1 to form a passivator; spin-coat the passivator on the perovskite light-absorbing layer 4 at a rotation speed of 3000 rpm, and anneal for 10 minutes at 100° C. to form a passivation layer 5 with a thickness of 3 nm.

[0056] A fullerene derivative with a thickness of 30 nm is prepared on the passivation layer 5 by vacuum evaporation as the electron transport layer 6 .

[0057] Copper with a thickness of 300 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0058] Example 7 CuI was sputtered on a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 250 nm by magnetron sputtering, and annealed at 290° C. for 32 minutes to prepare a hole transport layer 2 with a thickness of 40 nm.

[0059] Using isopropanol as solvent, a self-assembled monolayer spin-coating liquid with a concentration of 0.35 g / mL of 4PACz was prepared, and the self-assembled monolayer spin-coating liquid was spin-coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 minutes to form a self-assembled monolayer 3 with a thickness of 5 nm.

[0060] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, take (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 300 nm.

[0061] Using isopropanol as solvent, PEAI solution and mF-PEAI solution with a concentration of 0.5 mg / mL were prepared respectively, and the two were mixed in a volume ratio of 4:1 to form a passivating agent; the passivating agent was spin-coated on the perovskite light-absorbing layer 4 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 minutes to form a passivating layer 5 with a thickness of 4 nm.

[0062] A 20 nm thick SnO 2 is prepared on the passivation layer 5 by vacuum evaporation as the electron transport layer 6 .

[0063] Graphite with a thickness of 300 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0064] Example 8 On a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 350 nm, NiO is sputtered by magnetron sputtering. x , the value of x is 1 to 1.5, and the hole transport layer 2 with a thickness of 20 nm is prepared by annealing at 300°C for 30 minutes.

[0065] Using isopropanol as solvent, a self-assembled monolayer spin-coating liquid with a concentration of 0.3 g / mL of 2PACz was prepared, and the self-assembled monolayer spin-coating liquid was spin-coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 minutes to form a self-assembled monolayer 3 with a thickness of 4 nm.

[0066] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, take (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 600 nm.

[0067] Using isopropanol as solvent, a BAI solution and an mF-PEAI solution with a concentration of 0.5 mg / mL were prepared respectively, and the two were mixed in a volume ratio of 3.5:1 to form a passivating agent; the passivating agent was spin-coated on the perovskite light-absorbing layer 4 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 minutes to form a passivating layer 5 with a thickness of 5 nm.

[0068] TiO 2 with a thickness of 45 nm is prepared on the passivation layer 5 by vacuum evaporation as the electron transport layer 6 .

[0069] Amorphous carbon with a thickness of 400 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0070] Comparative Example 1 On a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 300 nm, NiO is sputtered by magnetron sputtering. x , the value of x is 1 to 1.5, and annealing is performed at 300° C. for 30 min to prepare a hole transport layer 2 with a thickness of 30 nm.

[0071] Using isopropanol as solvent, MeO-2PACz was prepared into a self-assembled monolayer spin coating liquid with a concentration of 0.3 g / mL, and the self-assembled monolayer spin coating liquid was spin coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 min to form a self-assembled monolayer 3 with a thickness of 2 nm.

[0072] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, take 100 μL (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm for 40 seconds. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 400 nm.

[0073] Using isopropanol as solvent, a PEACl solution with a concentration of 0.5 mg / mL was prepared as a passivating agent; the passivating agent was spin-coated on the perovskite light absorbing layer 4 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 minutes to form a passivating layer 5 with a thickness of 2 nm.

[0074] A C layer with a thickness of 40 nm was prepared on the passivation layer 5 by vacuum evaporation. 60 , as the electron transport layer 6.

[0075] Gold with a thickness of 100 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0076] Comparative Example 2 On a substrate 1 of transparent indium tin oxide conductive glass with a thickness of 300 nm, NiO is sputtered by magnetron sputtering. x , the value of x is 1 to 1.5, and annealing is performed at 300° C. for 30 min to prepare a hole transport layer 2 with a thickness of 30 nm.

[0077] Using isopropanol as solvent, MeO-2PACz was prepared into a self-assembled monolayer spin coating liquid with a concentration of 0.3 g / mL, and the self-assembled monolayer spin coating liquid was spin coated on the hole transport layer 2 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 min to form a self-assembled monolayer 3 with a thickness of 2 nm.

[0078] A mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 was used as solvent to prepare (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 Perovskite precursor solution, take 100 μL (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3 The perovskite precursor solution is coated on the self-assembled monolayer 3, and spin-coated at a rotation speed of 2000 rpm for 10 seconds, and then spin-coated at a rotation speed of 5000 rpm for 40 seconds. 15 seconds before the end of spin coating, 200 μL of chlorobenzene is added as an anti-solvent, and annealed at 100°C for 30 minutes to form a perovskite light-absorbing layer 4 with a thickness of 400 nm.

[0079] Using isopropanol as solvent, mF-PEAI solution with a concentration of 0.5 mg / mL was prepared as a passivating agent; the passivating agent was spin-coated on the perovskite light absorbing layer 4 at a rotation speed of 3000 rpm, and annealed at 100° C. for 10 minutes to form a passivating layer 5 with a thickness of 2 nm.

[0080] A C layer with a thickness of 40 nm was prepared on the passivation layer 5 by vacuum evaporation. 60 , as the electron transport layer 6.

[0081] Gold with a thickness of 100 nm was prepared on the electron transport layer 6 by vacuum plating as the top electrode 7 to obtain a double passivator perovskite solar cell.

[0082] In order to test the beneficial effects of the present invention, the performance test of Example 4 was compared with that of Comparative Examples 1-2, as shown in the following table:

[0083] The results show that the cell efficiency of the dual-passivator perovskite solar cell prepared in Example 4 of the present invention is significantly improved compared with the cell efficiency of Comparative Examples 1 and 2. Furthermore, it can be seen that the open circuit voltage in Example 4 is significantly improved, indicating its better defect passivation effect.

[0084] In summary, the present invention provides a dual-passivator perovskite solar cell and a preparation method thereof, by using one or more of PEACl, PEAI and BAI to cooperate with mF-PEAI to passivate the perovskite light-absorbing layer, different ions or related groups can be used to passivate more types of defects, thereby achieving better passivation, thereby increasing the output power of the solar cell. The preparation method is simple and has low condition requirements, and the efficiency of the prepared perovskite solar cell can reach 23.66%, further providing a good premise for the application of perovskite cells.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A double passivator perovskite solar cell, characterized in that: A passivating agent including one or more of PEACl, PEAI and BAI mixed with mF-PEAI is used as a passivating layer (5) to passivate the perovskite light absorbing layer (4).

2. The double passivator perovskite solar cell according to claim 1, characterized in that: It also comprises a substrate (1), and a hole transport layer (2), a self-assembled monolayer (3), a perovskite light absorption layer (4), an electron transport layer (6), and a top electrode (7) which are sequentially arranged on the substrate (1); the passivation layer (5) is arranged between the perovskite light absorption layer (4) and the electron transport layer (6).

3. The double passivator perovskite solar cell according to claim 2, characterized in that: The substrate (1) is a transparent conductive glass substrate.

4. The double passivator perovskite solar cell according to claim 2, characterized in that: The hole transport layer (2) is NiO x , CuSCN or CuI, where the value of x is 1 to 1.

5.

5. The double passivator perovskite solar cell according to claim 2, characterized in that: The self-assembled monolayer (3) is one or more of MeO-2PACz, 2PACz, Me-4PACz and 4PACz.

6. The double passivator perovskite solar cell according to claim 2, characterized in that: The perovskite light absorbing layer (4) is (FA 0.95 MA 0.05 ) 0.95 Cs 0.05 Pb(I 0.95 Br 0.05 )3.

7. The double passivator perovskite solar cell according to claim 2, characterized in that: The electron transport layer (6) is one of TiO2, SnO2, fullerene and a fullerene derivative.

8. The double passivator perovskite solar cell according to claim 2, characterized in that: The top electrode (7) is gold, silver, copper, graphite or amorphous carbon.

9. The double passivator perovskite solar cell according to any one of claims 1 to 8, characterized in that: The thickness of the passivation layer (5) is 1 to 5 nm.

10. A method for preparing a double passivator perovskite solar cell, characterized in that: include: Preparing a hole transport layer (2) on a substrate (1); Preparing a self-assembled monolayer (3) on the hole transport layer (2); Preparing a perovskite light absorbing layer (4) on the self-assembled monolayer (3); On the perovskite light absorbing layer (4), a passivation layer (5) is prepared using a passivation agent including one or more of PEACl, PEAI and BAI mixed with mF-PEAI; Preparing an electron transport layer (6) on the passivation layer (5); A top electrode (7) is prepared on the electron transport layer (6) to obtain a double passivator perovskite solar cell.

Citation Information

Patent Citations

  • Perovskite battery adopting 12-HSA passivated perovskite layer and preparation method

    CN116685158A

Cited By

  • Method for gas-phase passivation of perovskite thin film by diamine and perovskite solar cell

    CN121099873A